2016
DOI: 10.18765/jes.v32i2.6602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Tenure on the Adoption of Sawah Rice Production System in Nigeria.

Abstract: This study examined the effect of land tenure on the adoption of sawah rice production system in Nigeria. Using pre-tested interview guides, data were collected from 124 randomly selected sawah farmers. The results showed that rice farmers were predominantly male, married and had Quranic education, with the mean age of 42.30 years, farm sizes ranged from 0.03 to10 hectares (X = 0.5ha), the mean yield was 4.65 tonnes/ha, and the mean income was $1,041.38 ($1 = N145.00). The hierarchical regression analyses reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Oluwatayo et al (2019) reported that inheritance is the major form of land ownership in Nigeria. Similar results were presented by Eze et al (2011) and Alarima et al (2012). Purchase is land acquisition through outright purchase from the owner.…”
Section: Main Occupation Of Participants At Fgdssupporting
confidence: 84%
“…Oluwatayo et al (2019) reported that inheritance is the major form of land ownership in Nigeria. Similar results were presented by Eze et al (2011) and Alarima et al (2012). Purchase is land acquisition through outright purchase from the owner.…”
Section: Main Occupation Of Participants At Fgdssupporting
confidence: 84%
“…However, given the stipulation of the Nigerian Land Use Decree of 1978 that all land belongs to the government which holds the same trust for the public, the beneficiaries of the communal land allocation system are not formally recognized as the legal land right holders (Alarima et al, 2012). The government, therefore, has the sole right to allocate land to individuals and corporate entities based on the objectives of the interested parties (Oloyede et al, 2014).…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The green revolution package of high-yielding crop varieties (HYVs), irrigation and agrochemicals is mainly a technological intervention to boost food production, which can only be effective if properly communicated and disseminated to the farmers through appropriate channels. Sawah is a bunded, puddled and levelled field with inlet and outlet for irrigation and drainage (Alarima et al, 2016). Wakatsuki et al (2018) asserted that sawah rice farming system is the only solution to the long awaited green revolution in West Africa.…”
Section: Introductionmentioning
confidence: 99%